2011
DOI: 10.3402/ejpt.v2i0.5609
|View full text |Cite
|
Sign up to set email alerts
|

Brain stimulation in posttraumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) is a complex, heterogeneous disorder that develops following trauma and often includes perceptual, cognitive, affective, physiological, and psychological features. PTSD is characterized by hyperarousal, intrusive thoughts, exaggerated startle response, flashbacks, nightmares, sleep disturbances, emotional numbness, and persistent avoidance of trauma-associated stimuli. The efficacy of available treatments for PTSD may result in part from relief of associated depressive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 119 publications
(143 reference statements)
2
27
0
1
Order By: Relevance
“…PTSD is characterized by hyperarousal, intrusive vivid reliving of memories, and persistent avoidance of trauma-associated stimuli. 19–24,35 The estimated lifetime prevalence of PTSD in the United States is approximately 6.8%, and the 12-month prevalence is about 3.8%. 36,37 Unfortunately, 30% of patients still suffer from PTSD at least 10 years after the initial trauma despite the best current medical therapy.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…PTSD is characterized by hyperarousal, intrusive vivid reliving of memories, and persistent avoidance of trauma-associated stimuli. 19–24,35 The estimated lifetime prevalence of PTSD in the United States is approximately 6.8%, and the 12-month prevalence is about 3.8%. 36,37 Unfortunately, 30% of patients still suffer from PTSD at least 10 years after the initial trauma despite the best current medical therapy.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Epicranial stimulation (EpCS), is a minimally invasive technique of neuro-stimulation, where the electrode is placed over a cranial nerve (like occipital nerve) or over the dura mater and is electrically stimulated by the pulse generator 14). It has been utilized in refractory headache 15).…”
Section: Neuro-stimulaion Methodsmentioning
confidence: 99%
“…The areas of brain connected to vagus nerve which includes locus ceruleus, hippocampus, orbito-frontal cortex, amygdala and insular cortex are also responsible for processing the psycho-somatic elements of anxiety, making VNS to be a potential therapeutic modality in anxiety management 14,17). George et al .,17) in their pilot study of VNS in anxiety disorders, studied the short-term as well as long-term efficacy of VNS in patients of treatment resistant OCD, panic disorder and PTSD and found favorable outcomes.…”
Section: Brain Stimulation Treatment Of Anxiety Disordermentioning
confidence: 99%
“…Indeed, recent research on different memory disorders and symptomatic memory loss identified the beneficial effects of tDCS for memory disorders such as Alzheimer’s disease (Ferrucci et al, 2008; Bystad et al, 2016), post-traumatic stress disorder (Novakovic et al, 2011), psychiatric disorders which entail working memory loss, and memory loss resulting from brain damage induced by trauma or first-stroke episode (Jo et al, 2009; Clark and Parasuraman, 2014). In healthy subjects, use of tDCS in laboratory settings seems to improve both implicit and explicit memory (Coffman et al, 2014).…”
Section: Memory Enhancement With Tdcsmentioning
confidence: 99%